Immunosuppressive Therapy, 1987 - Kahan, Barry D. (1987)
The use of cyclosporine in transplant practice has at least doubled graft survival in renal transplantation, and has improved patient survival as well. In cardiac transplants, cyclosporine was first used in combination with prednisone to achieve immunosuppression by inhibition of the synthesis of lymphokines. When stimulated in vitro, lymphocytes from cyclosporine-treated patients display an impaired ability to produce the critical lymphokine interleukin-2. When there is in vitro inhibition, the patient shows poor immunosuppression in vivo. Unfortunately, cyclosporine is toxic: given in high enough doses to weaken the immune response, it can have neuroectodermal, and (of greater concern) mesenchymal side effects, including hepato- and nephrotoxicity. Patients who display renal impairment before cardiac transplantation are at a greater risk of postoperative renal dysfunction with cyclosporine therapy. The most important adverse actions of cyclosporine upon the nephron are events that arise from reduced renal blood flow caused either by vasoconstriction or by platelet adhesion associated with reduced prostacyclin production. The accepted technique for control of cyclosporine nephrotoxicity has been to reduce the cyclosporine dose, while simultaneously initiating azathioprine therapy. In the presence of an abnormal serum creatinine level, cyclosporine trough values appear to correlate with rejection or toxicity, thereby providing an indicator of drug-induced complications. Preoperative pharmacokinetic profiling to test cyclosporine clearance can help optimize the regimen in both renal and cardiac transplant patients. (Texas Heart Institute Journal 1987; 14:351-358)